Clinical characteristics of subglottic cancer: emphasis on therapeutic management strategies for stage II subglottic cancer*. (1st September 2020) - Komatsubara, Yasutoshi; Tachibana, Tomoyasu; Orita, Yorihisa; Makino, Takuma; Kuroda, Kazunori; Naoi, Yuto; Kataoka, Yuko; Sato, Yasuharu; Kariya, Shin; Nishizaki, Kazunori
Abstract: Background: Subglottic cancer (SGC) is extremely rare, as most laryngeal cancers are localized to the glottic region. Accordingly, the clinical characteristics of SGC have not been well characterized. Objectives: In the current study, SGCs were clinically evaluated, and the outcomes of radiotherapy (RT) in patients with stage II SGC were assessed. Materials and Methods: Medical data derived from 11 patients with SGC, who were treated at our hospital between 1995 and 2019, were retrospectively reviewed. Results: In our department SGC accounted for 3.9% of the 280 laryngeal cancer patients treated during the study period. At the time of SGC diagnosis, 9 (81.8%) had stage II cancer, 1 had stage III cancer, and 1 had stage IV cancer. Stage II SGC patients treated with concurrent chemoradiotherapy (CCRT) showed a significantly higher local control rate ( p = .026) and laryngeal dysfunction free rate ( p = .026) than those treated with RT alone. Salvage surgery, performed in 4 patients whose disease was not locally controlled with CCRT/RT, was successful in 3 patients. Conclusion: As a treatment strategy for stage II SGC, CCRT is an acceptable initial treatment for laryngeal function and preservation while salvage surgery is effective for recurrence after CCRT/RT treatment.